การออกแบบกราฟฟิกและมัลติมีเดียศูนย์ศึกษาประชาธิปไตย มหาวิทยาลัยธรรมศาสตร์ ศูนย์รังสิต - ศรมณี, กิตติ (Asian Creative Architecture, Art and Design, 2013)
บทคัดย่อ โครงการออกแบบกราฟฟิกและมัลติมีเดีย ศูนย์ศึกษาประชาธิปไตยมหาวิทยาลัยธรรมศาสตร์ ศูนย์รังสิต เป็นการร่วมงานของสำนักงานคณะกรรมการการเลือกตั้ง กับสถาบันเทคโนโลยีพระจอมเกล้าเจ้าคุณทหาร ลาดกระบัง โดยเล็งเห็นความสำคัญต่อการปลูกฝังการวางรากฐานให้ความรู้ระบอบการปกครองแบบประชาธิปไตยขึ้น ทั้งในส่วนกลางและส่วนภูมิภาค ศูนย์การเรียนรู้ย่อยในมหาวิทยาลัย โรงเรียนและชุมชน เพื่อให้เกิดเครือข่ายในการเรียนรู้ประชาธิปไตยและการเลือกตั้งอย่างมีระบบ เป็นการเตรียมความพร้อมให้กับเยาวชนและประชาชน ให้มีความเชื่อมั่นในหลักประชาธิปไตย คือความเท่าเทียมกันและความมีเสรีภาพ ตลอดจนมีความตระหนักในสิทธิและหน้าที่ของตนเอง ในการเป็นพลเมืองที่ดีของชาติ เพื่อเป็นศูนย์สำหรับการเผยแผ่และปลูกฝังการปกครองในระบอบประชาธิปไตย คุณลักษณะพิเศษของศูนย์ศึกษาประชาธิปไตย 1. เป็นศูนย์ที่สามารถศึกษาค้นคว้าได้ด้วยตัวเองผ่านสื่ออีเล็กทรอนิกส์ และโสต ทัศนูปกรณ์อันทันสมัย ที่มีระบบการนำเสนออันหลากหลาย อาทิ เกม ภาพยนตร์ แบบ ทดสอบด้วยตนเอง สถานีจำลองสถานการณ์จริง 2. เปรียบเสมือนห้องทดลอง (Live Discovery Library) ให้เยาวชนเข้ามาค้นคว้าและสัมผัสได้เหมือนจริง 3. เปรียบเสมือนห้องทดลองประชาธิปไตย ที่มาเสริมการเรียนการสอนประชาธิปไตยใน ระบบโรงเรียน 4. มีระบบทดสอบความรู้ด้วยตนเอง โดยจะได้รับประกาศนียบัตรรับรองผล หลังจากศึกษา ความรู้ผ่านครบทุกสถานีแล้ว 5. กระบวนการนำเสนอด้วยเทคโนโลยีระดับสูง มีความตื่นเต้นเร้าใจสนุกสนาน การออกแบบประกอบด้วย การออกแบบกราฟฟิกสัญลักษณ์สำหรับสิ่งพิมพ์ประชาสัมพันธ์ หนังสือคู่มือการเข้าเยี่ยมชมประจำศูนย์ศึกษาประชาธิปไตย และบอร์ดนิทรรศการต่างๆ ซึ่งแบ่งออกเป็น 4 สถานี 2 ห้องสาธิตการเลือกตั้ง และการออกกฎหมายการออกแบบมัลติมีเดียประกอบไปด้วยชุดมัลติมีเดียเมจิกวิชันประกอบการแสดงในห้องฉายภาพยนตร์วิวัฒนาการการเมืองไทย ภาพยนตร์อนิเมชัน 9 เรื่อง อธิบายสิทธิและหน้าที่ของพลเมืองไทย วิดีทัศน์ผลเสียขที่เป็นเยาวองการไม่ไปใช้สิทธิเลือกตั้ง วิดีทัศน์รัฐสภา อธิบายบทบาทและหน้าที่ของรัฐสภาไทย การออกแบบทั้งหมดมุ่งเน้นกลุ่มเป้าหมายชน ซึ่งเป็นกลุ่มเป้าหมายหลัก ง่ายต่อการบ่มเพราะจิตสำนึกแห่งความเป็นประชาธิปไตย คำสำคัญ: ประชาธิปไตย การเรียนรู้ เยาวชน กราฟฟิก มลติมีเดีย Abstract The Graphic and Multimedia Design project has been organized by the Democracy Education Center of Thammasat University, Rangsit Center in cooperation with the Office of the Election Commission of Thailand and King Mongkut Institute of Technology, Ladkrabang is order to develop better understanding of democracy at the national and provincial levels, particularly through the university’s branch campuses, and local schools and communities. The objective is to create a network that can work to develop a better understanding of democratic principles and the country’s electoral system to prepare the public, especially youth for future elections. They must be taught to believe and trust in democracy, equality and freedom and what rights and responsibilities these bring to each individual, as at the end, the country will also benefit. The Democracy Center has as it objective the promotion and dissemination of information on democracy and democratic principles. Its distinctive features include: 1. Serve as a study and research center using advanced information technology to provide access to online information and audio-video programming. Materials include online games, videos, films and live broadcasts through various networks 2. Live Discovery Library that youth can access for research. 3. Democracy laboratory to promote and support education on democracy in schools. 4. Individual learning-testing program that has been approved by various education departments 5. Introduction of more advanced technology that can make learning more fun and effective. The attached graphic design has been developed for promotional print material. The guidebook will be available at the Democracy Education Center along with exhibition boards to be placed at four locations with two demonstration venues, one focusing on elections and one on legislation. The multimedia productions can be presented in a room equipped with projector and screen called “The Evolution of Democracy in Thailand”. The productions will include nine animated films that explore the meaning of democracy and the right and responsibility to vote, a video that tells about the problems caused when people do not exercise their right to vote and a video on the Thai Parliament and its roles and responsibilities. All the graphic and multimedia materials are aimed a Thai youth who are the most important target group as they are the easiest to influence, and, therefore, it is vital that they understand and will support democratic principles. Keywords: Democracy Education Youth Graphic Multimedia